ANALISIS PENGEMBANGAN MODEL MATAKULIAH PRAKTIK PADA PROGRAM STUDI ILMU PEMERINTAHAN UNIVERSITAS TERBUKA - Siti Aisyah; Enceng Enceng (LPPM Universitas Terbuka, 2018)
The problem in developing practical courses at universities that apply the distance education in Indonesia are: 1)It is difficult to determine the place of practice for students because students are spread in different locations; 2)The study program found it difficult to develop a practice course in distance education methods. The development of subject matter practice in the government science study program at Universitas Terbuka has a significant urgency with the needs of the people in Indonesia. This article aims to analyze the development of practical courses in government science study programs, in Universitas Terbuka.This article is the result of a research with a qualitative approach. Primary data obtained from interviews with experts, students, and graduate users. Secondary data includes the results of the literature review, the results of previous studies, and documents relating to practical subjects. The research findings are: 1)Mastery of students in understanding governance as science and art implies not only at the level of mastery of theory and concepts, but also the importance of prioritizing attitude skills and behavior in dealing with government phenomena. 2)The subject matter which has the potential to be developed into practice material is a course related to development, village government, the legislature, and the methodology of governmental science. The implication of this finding is the need to conduct a comparative study in the application of practical subjects at several other universities that use distance learning methods both domestically and abroad.